Hubungan Antara Gaya Mengajar Guru dan Hasil Belajar Tajwid Siswa Kelas VII Madrasah Tsanawiyah - Rafsan, Muhammad; Shalih, Badrus (SENTRI: Jurnal Riset Ilmiah, 2025)
This study is motivated by the paradox between the high intensity of Quranic learning at pesantren-integrated madrasahs and the persistently low Tajwid proficiency among students 62% of Grade VII students at MTs Darullughah Waddawah Pasuruan failed to meet the minimum Tajwid competency standard. Prior studies have primarily examined the effect of teaching methods on Tajwid learning in general, without specifically addressing the relationship between teaching styles and Tajwid outcomes in a pesantren-integrated MTs context. This study aims to analyze: (1) the profile of teachers' teaching styles; (2) students' Tajwid learning achievement; and (3) the relationship and contribution of teaching styles to Tajwid learning outcomes. A quantitative correlational design was employed with proportionate stratified random sampling (n = 74 from a population of 280). Data were collected through a validated teaching-style questionnaire (37 items, α = .891), a Tajwid achievement test (28 items, α = .876), and supporting interviews. Pearson correlation and simple linear regression were used for analysis. Results indicate a positive and significant relationship (r = .672; p < .05), with teaching style accounting for 45.2% of the variance in Tajwid learning outcomes. Theoretically, this study contributes by integrating Grasha's (1996) teaching-style theory with Gardner's multiple intelligences framework within the pesantren-integrated MTs context, proposing a linguistic-musical intelligence-based teaching-style model not previously examined in Indonesian Islamic education research.